2015
DOI: 10.1016/j.febslet.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

C‐peptide evolution: Generation from few structural restrictions of bioactivities not necessarily functional

Abstract: a b s t r a c tThe proinsulin C-peptide has molecular, cellular and organismal activities but lacks diseaseassociated mutations or short-term loss-of-function effects. This dilemma between activity and function may be explained from its evolutionary setting with insulin as an ancestral partner. The charge, approximate length and flexibility of C-peptide are all that is required for the insulin interactions, while remaining aspects are free to evolve, where new bioactivities can emerge. They can initially be tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A consistent observation in the emerging field of C-peptide endocrinology is the lack of strong conservation of its amino acid residue sequence, compared to that of the insulin A and B chain, across the vertebrates [99,100]. For a recent excellent review of the structure-activity relationship of C-peptide, see Landreh et al [101].…”
Section: C-peptide Sequence Conservation In the Great Apes Including mentioning
confidence: 98%
“…A consistent observation in the emerging field of C-peptide endocrinology is the lack of strong conservation of its amino acid residue sequence, compared to that of the insulin A and B chain, across the vertebrates [99,100]. For a recent excellent review of the structure-activity relationship of C-peptide, see Landreh et al [101].…”
Section: C-peptide Sequence Conservation In the Great Apes Including mentioning
confidence: 98%
“…Finally, the existence of C-peptide across all vertebrates as a connecting peptide in proinsulin still suggests a surprising resilience to evolutionary elimination, and is in contrast to its sequence variability. [11] -No phenotype identified for C-peptide mutations [54] Presence -A C-peptide segment present in proinsulins across all phyla [20] -C-peptide segments are poorly conserved [27] Requirements -C-peptide required for correct folding of proinsulin and prevents insulin aggregation in vitro [45,52] -C-peptide mutations do not impair insulin biogenesis [54] Interactions -C-peptide binds to cell membranes and activates MAP kinases [16,17,31,34] -A C-peptide receptor not conclusively identified [56] Neurological effects -C-peptide reduces neuropathy and influences nerve conductivity in individual DMT1 patients [12] -No beneficial effects on nerve function observed in largescale clinical trials [23] Cellular effects -C-peptide elicits a broad range of cellular effects in tissue cultures and rodent models [10] -In vitro C-peptide effects exhibit only limited specificity for peptide sequence or chirality [14]…”
Section: Is C-peptide Redundant?mentioning
confidence: 99%
“…On the contrary, an additional hormonal activity with biological relevance has still not been established, even if not yet fully excluded at a small scale. Instead, evolutionary explanations now remain [19,20], and are of interest regarding distinctions between activities and functions of peptides in general. Other interest in C-peptide now appears to have faded out [21] when the latest clinical tests also failed to show a clear, hormonal function [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…C‐peptide participation in proinsulin structure fulfills the important biological role of facilitating the formation of the correct secondary and tertiary structure of insulin and preventing insulin aggregation . Recent studies have reported several molecular interactions of C‐peptide, cell signaling events, and pivotal effects in diabetic patients …”
Section: Introductionmentioning
confidence: 99%